Exploring The Influence of Project for Strengthening the Profile of Pancasila Students and School Culture to Character Building: The Mediating Role of Student Self-Awareness - Andika Ikhfa Nurdian; Panggih Wahyu Nugroho; Noorazman Bin Abd Samad; Rihab Wit Daryono (Universitas PGRI Yogyakarta, 2024)
Self-awareness plays an important role in helping students understand and enable them to apply their values, beliefs and attitudes towards Pancasila and school culture. This research aims to explore the Project for Strengthening the Pancasila Student Profile (P5) and school culture in shaping student character through student awareness at MTsN 10 Magetan. The survey method was used by purposive sampling of 298 students. PLS-SEM analysis was carried out to test the conceptual model and analyze the data. The results show that the P5 has a positive impact on students' character formation, with self-awareness playing a mediating role between